Consumo y prácticas sociales "ocultas": la prostitución - Rubio Arribas, Fco. Javier (Nómadas. Critical Journal of Social and Juridical Science, 2012)
From the psychosocial point of view, people who exercise prostitution constitute a heterogeneous group with important differences in their reactions and in the practices of this profession. There are three main social actors: people who exercise the prostitution (mostly women), the clients and pressure groups (mafias, networks and procurers). Social stigma becomes evident, above all in some types of exercises, such as street prostitution, and some clubs (lesser category) where most of the women have a high risk of social exclusion. The rest of the modalities (club of high standing, luxury prostitution, flats, virtual services, etc) characterize by a greater privacy, concealment and a double life escape this stigma. Prostitution is done for money. That is, for the same reason that any socially devalued activity is carry out. So, the need to obtain incomes is present in most of the paths that lead to prostitution.
Keywords: prostitution; sexual exploitation; consumption of prostitution; clients of prostitution; sex workers; new profiles of workers; social stigma of the prostitute.